1997
DOI: 10.1017/s0252921100071438
|View full text |Cite
|
Sign up to set email alerts
|

High-Velocity Clouds and their Soft X-ray Emission

Abstract: Abstract. Diffuse excess 1/4 keV soft X-ray emission was found to be positionally correlated with the column density distribution of the high velocity cloud (HVC) complex C (Kerp et al. 1996). Here we point out that the detected diffuse X-ray emission is indeed associated with the HVC phenomenon. For this purpose we study the 1/4 keV radiation transfer as well as the Hi column density distribution of HVCs and intermediate velocity clouds (IVCs) towards HVC complex C in detail. We present evidence that on arcmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…They possibly represent one group of local analogues of extra-planar gas features seen in the vicinity of other galaxies. IVCs and HVCs represent multi-phase structures that can contain regions of partly molecular gas (H 2 absorption, Richter et al 2001a;Wakker 2006), cold and warm neutral gas seen in 21-cm emission Ben Bekhti et al 2008), warm-ionised plasma as traced by Hα emission (Putman et al 2003;Hill et al 2009) and UV absorption (Lu et al 1994), and highly-ionised plasma seen in O vi absorption (Sembach et al 2003;Fox et al 2006) and in X-ray emission (Kerp et al 1999;de Boer 2004, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…They possibly represent one group of local analogues of extra-planar gas features seen in the vicinity of other galaxies. IVCs and HVCs represent multi-phase structures that can contain regions of partly molecular gas (H 2 absorption, Richter et al 2001a;Wakker 2006), cold and warm neutral gas seen in 21-cm emission Ben Bekhti et al 2008), warm-ionised plasma as traced by Hα emission (Putman et al 2003;Hill et al 2009) and UV absorption (Lu et al 1994), and highly-ionised plasma seen in O vi absorption (Sembach et al 2003;Fox et al 2006) and in X-ray emission (Kerp et al 1999;de Boer 2004, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the extragalactic background can be used as a "reference" to normalize the intensities of the XRB (see Sect. 4), as has been done in previous investigations using ROSAT data (e.g., Kerp et al 1999;Snowden et al 1998;Pradas et al 2003). Energy bands C1, C2 and C3 are only related to source detection and proton flare filtering.…”
Section: Selection Of the Energy Bandsmentioning
confidence: 81%
“…Read & Ponman (2003) published background maps to correct the observations for vignetting, which is of special importance for the analysis of extended sources. But the contribution of the cosmic X-ray background, originating from the Local Hot Bubble, the Galactic Halo and the extragalactic X-ray background, has not been systematically treated for XMM-Newton as it has been in case of the ROSAT mission (e.g., Kerp et al 1999;Snowden et al 1998;Pradas et al 2003). Because XMM-Newton is, in principle, able to detect very faint signals, all systematic effects must be well understood and Tables 3-6 are only available in electronic form at http://www.edpsciences.org reliable methods to eliminate their contributions have to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Hirth et al (1985) and Kerp et al (1999) showed an excess of X-ray emission that seems to be spatially correlated with Complex C, but no clear relationship with Draco itself could be established. On the other hand, based on FUV observations, Park et al (2009) reported the detection of several ionic lines in the direction of Draco, especially C IV, Si II, and O III].…”
Section: Hot Gasmentioning
confidence: 97%